1975
DOI: 10.3758/bf03204105
|View full text |Cite
|
Sign up to set email alerts
|

Depth adjacency and the rod-and-frame illusion

Abstract: In Experiment I, the tactile adjustment of a comparison bar was used to measure the change in the rod-and-frame illusion as a function of the stereoscopic position of the rod relative to the frame. A vertical rod was presented at a near, a middle. or a far distance, with a single frame tilted counterclockwise at the near distance. a single frame tilted clockwise at the far distance. or two frames of opposite tilt presented simultaneously at the near and far distances. When only one frame was present. displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
2

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
3
30
2
Order By: Relevance
“…Likewise, the results of Experiment 2, Figure 1, also fail to confirm this possibility since frames of equal retinal size but at different distances yielded equivalent RFEs. It is conceivable that the different methods of measuring the RFE in the present study and that of Gogel and Newton (1975) may somehow contribute to the disparate results, but in any event, without further confirmation, the proposed role of distance in the RFE is dubious.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…Likewise, the results of Experiment 2, Figure 1, also fail to confirm this possibility since frames of equal retinal size but at different distances yielded equivalent RFEs. It is conceivable that the different methods of measuring the RFE in the present study and that of Gogel and Newton (1975) may somehow contribute to the disparate results, but in any event, without further confirmation, the proposed role of distance in the RFE is dubious.…”
mentioning
confidence: 46%
“…The conclusion to be drawn is that retinal size controls the RFE. This has several implications, one of which relates to the proposal of Gogel and Newton (1975) that the RFE should increase with increasing convergence distance to the rod, given that the relative depth between rod and frame and frame-tilt magnitude were held constant. The results of Experiment 1, shown in Table 1, given no indication of such an outcome even though large variations in both convergence and apparent distance had occurred.…”
mentioning
confidence: 99%
“…This was equivalent to the maximum depth separation examined by Gogel and Newton (1975). Figure 2 shows the relative positions of rod and frame in the POP studies.…”
Section: Apparatusmentioning
confidence: 99%
“…Yet, Gogel and Newton (1975) have shown that, with an upright rod and tilted frame set stereoscopically at 100 and 160 em, respectively, perceived rod tilt diminished significantly relative to a coplanar condition. Since the display used by Gogel and Newton (1975) projected about 10 deg of arc sidet , it is possible that the reduced illusion they obtained belonged to the domain of small-frame phenomena in which the line" and frame produce an orientation contrast illusion This research was supported in part by NIH Grant EY02264. S. M. Ebenholtz's mailing address is: Department of Psychology, University of Wisconsin, Madison, Wisconsin 53706.…”
mentioning
confidence: 99%
See 1 more Smart Citation